Digital Technology Based Halal Certification Model in Nigeria: Exploring the Potential of Blockchain for Transparency and Anti-Fraud Measures - Taofeek Muhammed Thani (Raudhatun Najah Publisher, 2026)
The halal certification system in Nigeria currently faces serious challenges, including weak transparency, vulnerability to document falsification, and limited supply-chain oversight, whereas ideally halal certification should ensure authenticity, accountability, and public trust throughout the entire value chain. This study aims to develop a conceptual model of digital halal certification that aligns with Nigeria’s social, economic, and regulatory context. The research employs a qualitative approach through a literature review by examining Nigerian halal policies, institutional reports, and recent scholarly publications on blockchain and halal management; the data were then analyzed using content analysis supported by theoretical triangulation. The findings indicate that blockchain has significant potential to enhance transparency, tracking accuracy, and fraud prevention within Nigeria’s halal ecosystem, although its implementation requires regulatory readiness, technical capacity, and stakeholder collaboration. The study recommends the development of a context-appropriate blockchain architecture for halal certification, the implementation of pilot projects to assess technical effectiveness, and the formulation of policy frameworks that support long-term adoption of this technology in the national halal certification system.